Karyotypes and Morphological Variability of Crayfish Pontastacus leptodactylus and P. angulosus (Malacostraca, Decapoda) - Kostyuk, V.S.; Garbar, A.V.; Mezhzherin, S.V. (Вестник зоологии, 2013)
The existence on the territory of Ukraine of two sympatric widespread species definitely different by their chromosome number was proved based on the meiotic chromosome preparations. Besides the nominal species Pontastacus leptodactylus (Dana, 1852) with modal haploid chromosome number n = 93 we prove the existence of P.?angulosus (Rathke, 1837) with n = 88. На основании анализа мейотических хромосомных препаратов доказано существование в Украине двух симпатрических широко распространённых видов, которые чётко отличаются по числу хромосом. Кроме номинативного длиннопалого рака, Pontastacus leptodactylus (Dana, 1852), с модальным числом хромосом в гаплоидном наборе на уровне n = 93 доказано присутствие и угластого рака, P. angulosus (Rathke, 1837), с модальным значением n = 88.